PENGGUNAAN METODE KECERDASAN BUATAN RUNUT MAJU DALAM MEMECAHKAN PERMASALAHAN GAME LABIRIN - Santi Astawa, I Gede (Jurnal Ilmu Komputer, 2012)
Games are an application that is quite attractive because it can be used for refreshing. Maze game is an example of a simple game that aims to determine the appropriate steps to achieve its intended purpose. Maze created in coordinates (x, y), with the known facts are the coordinates of obstacles, and the coordinates of current location, its main task is to find a way out. In this discussion, maze solved using artificial intelligence modeling (forward reasoning).
Keywords: Maze, Artificial intelligence modelling, forward reasoning